2020
DOI: 10.1080/2162402x.2020.1828538
|View full text |Cite
|
Sign up to set email alerts
|

Significantly different immunological score in lung adenocarcinoma and squamous cell carcinoma and a proposal for a new immune staging system

Abstract: TNM stage is not enough to accurately predict the prognosis of patients with non-small cell lung cancer (NSCLC). This study aimed to establish the Immunoscore (IS) in lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC), separately, and propose a new staging system in NSCLC. We used the multiplex fluorescent immunohistochemistry (mIHC) technology to detect 17 immune biomarkers of 304 patients with NSCLC. The LASSO-COX regression model was used to establish the IS NSCLC in the training cohorts. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 54 publications
0
14
1
Order By: Relevance
“…Previous studies have found that the immunoscores of lung squamous cell carcinoma and lung adenocarcinoma are significantly different, and the different tumor-infiltrating immune cell indicate different prognosis in LUSC and LUAD ( 20 , 21 ). So we analyze immune correlation of NUF2 in LUSC and LUAD respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have found that the immunoscores of lung squamous cell carcinoma and lung adenocarcinoma are significantly different, and the different tumor-infiltrating immune cell indicate different prognosis in LUSC and LUAD ( 20 , 21 ). So we analyze immune correlation of NUF2 in LUSC and LUAD respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Three distinct subtypes of LUAD were introduced in 2014, including proximal inflammatory (PI), proximal proliferative (PP), and terminal respiratory unit (TRU) ( 43 ). LUAD usually arises from the distal airway, while LUSC is associated with more proximal airways ( 44 ). LUSC is generally more strongly associated with smoking and inflammatory diseases than LUAD ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…LUAD usually arises from the distal airway, while LUSC is associated with more proximal airways ( 44 ). LUSC is generally more strongly associated with smoking and inflammatory diseases than LUAD ( 44 ). In general, LUAD grows more slowly and has smaller lumps than its contemporaneous counterpart LUSC but tends to metastasize at an early stage ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Inoue, Y et al’s study reported that high CD73 expression was an independent unfavorable prognostic marker in LUAD ( Inoue et al, 2017 ). However, Zeng, Z et al’s study reported that CD73 were associated with favorable prognosis in LUAD ( Zeng et al, 2020 ). Thus, the prognostic value of CD73 in LUAD still needed further studies.…”
Section: Discussionmentioning
confidence: 99%